IMPLEMENTASI METODE EDUTAINMENT DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL DI KELAS V SEKOLAH DASAR - Rahayu, Rima Agusyulia; Dewi, Ratna Sari; Hakim, Zerri Rahman (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to explore the implementation of the edutainment method in teaching Integrated Science and Social Studies (IPAS) at SD Negeri Margasana 1. The findings indicated that this method had a positive impact on the learning process. The use of edutainment effectively increased students’ engagement in both individual and group activities, as reflected in their more active participation, higher enthusiasm, and deeper understanding of the material. In the planning stage, teachers appropriately adapted the edutainment method by designing lesson plans that emphasized interactivity, creativity, and the use of supportive learning media to create an enjoyable learning environment. The implementation was carried out through communicative and persuasive approaches, with the teacher acting as a facilitator guiding students throughout the learning process. Evaluation involved various forms of assessment, including formative tests, project-based tasks, and observations of student participation, providing a comprehensive picture of students’ development. The implementation of this method supports not only academic achievement but also the development of social skills, communication skills, teamwork, and creativity. However, challenges remain, particularly in providing adequate facilities and learning media to optimize the use of the edutainment method.